Climate, Energy and Water : Managing Trade-offs, Seizing Opportunities - Pittock, Jamie; Hussey, Karen; Dovers, Stephen (Cambridge : Cambridge University Press, 2015)
With the global population expected to reach nine billion by 2050, our capacity to provide enough food, water and energy relies on our understanding and management of the complex interdependencies in the climate-energy-water nexus. This book presents a comprehensive and up-to-date analysis of the interdependencies between these sectors and the knock-on consequences of those interactions for other sectors, such as food production and biodiversity conservation. The interdisciplinary nature of the book across the three sectors of climate, energy and water means that it will be valuable for advanced students, researchers and policymakers across a broad range of fields, including environmental/energy/water/climate policy, environmental economics, climate science, hydrology, ecology and geography.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Climate change mitigation